Correlation of C3c complement, NT-pro BNP and Left Ventricle Ejection Fraction in Heart Failure - Julious, Julious; Nugraha, Jusak; Aminuddin, Mohammad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Introduction. Heart failure is a health problem in Indonesia. The 2013 Basic Health Research Data showed that the estimated heart failure in Indonesia was 530,068 people. Echocardiography examination which has been a routine examination of heart failure patients is not necessarily available in all hospitals, so that a more applicable and inexpensive alternative examination is needed. Previous studies have shown an increase in C3c levels associated with improved survival and better cardiac remodeling. On this basis, this research needs to be performed in order to determine the correlation between C3c complement levels, NT-proBNP and LVEF in heart failure patients. Method. A cross-sectional study was conducted at the Dr Soetomo Hospital between August 2018 to September 2018 with 30 samples. Samples were taken consecutively from patients with heart failure who were treated at the integrated heart service center. Examination of C3c complement, NT-proBNP and echocardiography (LVEF data) was carried out in all patients. Result. The result of this study showed no significant correlation between C3c complement and NT-proBNP (r = -0.253, p = 0.177). The correlation between C3c complement and LVEF was also not significant (r = -0.074, p = 0.696). A significant moderate correlation between NT-proBNP and LVEF was found (r = -0.444, p = 0.014). Conclusion. The C3c complement could not be used as an alternative examination for NT-proBNP and LVEF. The limitations of the study were heterogeneous sample characteristics. A further study with more stringent criteria is needed to minimize the bias of examination results.